Formation of carbonate pipes in the northern Okinawa Trough linked to strong sulfate exhaustion and iron supply. (15th May 2017) - Peng, Xiaotong; Guo, Zixiao; Chen, Shun; Sun, Zhilei; Xu, Hengchao; Ta, Kaiwen; Zhang, Jianchao; Zhang, Lijuan; Li, Jiwei; Du, Mengran
Abstract: The microbial anaerobic oxidation of methane (AOM), a key biogeochemical process that consumes substantial amounts of methane produced in seafloor sediments, can lead to the formation of carbonate deposits at or beneath the sea floor. Although Fe oxide-driven AOM has been identified in cold seep sediments, the exact mode by which it may influence the formation of carbonate deposits remains poorly understood. Here, we characterize the morphology, petrology and geochemistry of a methane-derived Fe-rich carbonate pipe in the northern Okinawa Trough (OT). We detect abundant authigenic pyrites, as well as widespread trace Fe, within microbial mat-like carbonate veins in the pipe. The in situ δ 34 S values of these pyrites range from −3.9 to 31.6‰ (VCDT), suggesting a strong consumption of seawater sulfate by sulfate-driven AOM at the bottom of sulfate reduction zone. The positive δ 56 Fe values of pyrite and notable enrichment of Fe in the OT pipe concurrently indicate that the pyrites are primarily derived from Fe oxides in deep sediments. We propose that the Fe-rich carbonate pipe formed at the bottom of sulfate reduction zone, below which Fe-driven AOM, rather than Fe-oxide reduction coupled to organic matter degradation, might be responsible for the abundantly available Fe 2+ in the fluids from which pyrites precipitated. The Fe-rich carbonate pipe described in this study probably represents the first fossil example of carbonate deposits linked to Fe-driven AOM. Because Fe-rich carbonate deposits have also been found at other cold seeps worldwide, we infer that similar processes may play an essential role in biogeochemical cycling of sub-seafloor methane and Fe at continental margins.